Legal Reform of Indonesia’s Nickel Export Ban (Indonesia-Europa) - Lestari, Putri Diah; Ilmania, Nurika Falah; Al-Haq, Mursyid (SASI, 2024)
Introduction: Indonesia's nickel export restriction policy is regulated in the Minister of Trade Regulation No. 96 of 2019 concerning Export Requirements for Mining Products from Processing and Refining which is in line with the Minister of Energy and Mineral Resources Regulation No. 11 of 2019 and is the cause of a lawsuit brought by the European Union to the WTO for Indonesia's violation of the provisions of Article XI.1 of the GATT 1994 WTO agreement related to discrimination against export products in the form of nickel ore.Purposes of the Research: The purpose of this research is to analyze the rules of the prohibition of Nickel Exports Based on International Law reviewed based on the theory of state sovereignty in Indonesia.Methods of the Research: This research uses normative legal research using a statutory approach and conceptual approach, and uses descriptive analysis techniques supported by two legal materials, namely primary legal materials and secondary legal materials.Results of the Research: Indonesia certainly has a strong reason why these restrictions are carried out. In addition to national economic growth, it also realizes sustainable development. This research is conducted to describe the policy through the lens of international trade law and Indonesia's authority as a sovereign state.